Geogrid-type geotextile made from Typha domingensis fibers with high tensile strength for erosion control - Luiz Diego Vidal Santos; Francisco Sandro Rodrigues Holanda; Alceu Pedrotti; Janisson Bispo Lino; Cátia dos Santos Fontes; Jeangela Carla Rodrigues de Melo; Regina Helena Marino; Gizelio Menzes Boge (Invention Disclosure)
The present invention relates to a geotextile of the geogrid type manufactured with fibers from the Typha domingensis plant, known as cumbungi, recognized for its remarkable tensile strength. This geotextile is developed to mitigate erosive processes and is produced from natural fibers arranged in a mat configuration. This product fit in with the technical fields of civil engineering and textile materials. The central innovation of this geotextile lies in the provision of a natural alternative featuring biodegradable fibers and high tensile strength. Its applications in environmental engineering include erosion prevention, slope stabilization, and reinforcement of road structures, with the fundamental goal of preserving the soil against degradation and erosion. This high-strength geotextile is composed of Typha domingensis fibers skillfully interwoven and connected to form a grid structure, with each unit covering approximately 0.25 m2s. Furthermore, a double layer of waterproofing material is incorporated to provide greater cohesion, environmental durability, and tensile strength. In practical applications, this geotextile demonstrates a remarkable ability to withstand mass movements even before local vegetation develops. This makes it a technological alternative that synergistically combines technological and ecological processes, incorporating the principles of soil bioengineering while offering a sustainable alternative to synthetic geotextiles. The use of this geotextile in the field is preferably combined with living components such as seeds, plant stakes, wood, or rocks for slope or embankment stabilization, with a primary focus on effective erosion control and the promotion of environmental sustainability.